Respiratory rehabilitation for Covid-19 related persistent dyspnoea: A one-year experience. (November 2021) - Bouteleux, Benoit; Henrot, Pauline; Ernst, Rachel; Grassion, Léo; Raherison-Semjen, Chantal; Beaufils, Fabien; Zysman, Maéva; Delorme, Mathieu
Abstract: Background: Growing consideration is emerging regarding the burden of persisting sequelae after SARS-CoV-2 infection. Out-patients exhibiting long Covid may benefit from ambulatory rehabilitation which is, to date, poorly documented. Methods: A longitudinal follow-up over a one-year period was conducted in two ambulatory rehabilitation structures in order to describe the characteristics of real-life patients referred with Covid-19 sequelae and their evolution over the course of rehabilitation. Results: 39 consecutive patients were included from April 1st, 2020 to April 1st, 2021. Patients were middle-aged (48 ± 15yr), without comorbidities, and mostly mild to moderate SARS-CoV-2 infection (25(64%) not requiring hospitalisation). Rehabilitation referral was considered with a median delay of 73[34–178] days after disease onset. Most prevalent symptoms were dyspnoea (n = 35(90%)) and fatigue (n = 30(77%)). Hyperventilation syndrome was highly frequent (n = 12(34%)). 29(74%) patients presented with prolonged functional sequelae, which was associated with younger age (43 ± 14 vs . 50 ± 10yr; p = 0.002), greater prevalence of hyperventilation syndrome (n = 12(41%) vs . 0(0%); p = 0.255) and poorer quality of life (VQ-11; 31 ± 10 vs . 23 ± 9; p = 0.030). Over the course of rehabilitation, exertional dyspnoea, 6-min walking distance, 3-min sit-to-stand test, hyperventilation syndrome prevalence and quality of life significantly improved. Conclusion: Hyperventilation is frequent in long Covid and may explain persistent dyspnoea as well as altered quality of life. Our data support screening of hyperventilation syndrome and functional impairment in mild Covid-19 out-patients as both of these components may improve with ambulatory rehabilitation. Highlights: COVID-19 out patients without severe initial manifestation may have prolonged sequelae. Main symptoms in COVID-19 out patients are dyspnoea and fatigue. Prevalence of hyperventilation syndrome is substantial in Covid-19 out patients. Respiratory rehabilitation may improve dysfunctional breathing, functional capacities and quality of life.